2021
DOI: 10.4274/ejbh.galenos.2021.2021-5-6
|View full text |Cite|
|
Sign up to set email alerts
|

New Data on the Epidemiology of Breast Implant- Associated Anaplastic Large Cell Lymphoma

Abstract: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare form of non-Hodgkin's T-cell, CD30-positive, and anaplastic lymphoma kinase-negative lymphoma that develops around breast implants, especially those with a textured surface, used in both cosmetic surgery and reconstructive surgery (1, 2). The first case was reported in 1997 by Keech and Creech (3). In June 2011, the Food and Drug Administration (FDA) identified for the first time a possible association between breast implants and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
(38 reference statements)
2
16
0
Order By: Relevance
“…Amongst other reasons this leads to an underreporting of cases as a comparison of the countries exemplifies. Australia reported a total of 112 cases over 25 million inhabitants 52 , while the United States found only 384 cases with 330 million inhabitants 38 , depicting a strong percental difference. Consequently standardized and legal binding registries will be the only way to acquire international comparable data 53 and contribute to the pathophysiology including genetic predisposition and implant surface texture 48,54 .…”
Section: Discussionmentioning
confidence: 98%
“…Amongst other reasons this leads to an underreporting of cases as a comparison of the countries exemplifies. Australia reported a total of 112 cases over 25 million inhabitants 52 , while the United States found only 384 cases with 330 million inhabitants 38 , depicting a strong percental difference. Consequently standardized and legal binding registries will be the only way to acquire international comparable data 53 and contribute to the pathophysiology including genetic predisposition and implant surface texture 48,54 .…”
Section: Discussionmentioning
confidence: 98%
“…A study from de Boer et al showed that BRCA 1/2 mutation carriers with implants have an increased risk of BIA-ALCL [ 13 ]. Moreover, Ionescu et al found that the absolute risk of developing BIA-ALCL in women with BRCA 1/2 mutations with breast implants was 1/1551 at 75 years of age compared with 1/7507 in women from the general population [ 60 ]. Women diagnosed with Li-Fraumeni syndrome, a cancer-predisposing condition caused by germline pathogenic mutations in TP53 , have been reported to develop BIA-ALCL, perhaps suggesting that they may also be at greater risk [ 61 , 62 ].…”
Section: Genetics and Bia-alclmentioning
confidence: 99%
“…In this vein, the total number of BIA-ALCL cases worldwide is difficult to determine due to (i) a lack of information regarding the number of people with breast implants in situ and (ii) a limited awareness of BIA-ALCL by surgeons and patients leading to large discrepancies in the reporting of cases. 78 This is likely exacerbated by the fact that BIA-ALCL has a long latency of around 5 to 10 years and can present with a wide variety of symptoms. As such, the absolute risk of developing BIA-ALCL is the subject of much debate.…”
Section: Breast Implant-associated Lymphomamentioning
confidence: 99%